Academician Nikolai Nikodimovich Malinovsky (1921–2018) (to the 100th anniversary of the birth) - A. A. Kurygin; V. V. Semenov; I. S. Tarbaev (Вестник хирургии имени И.И. Грекова, 2021)
Professor Nikolai Nikodimovich Malinovsky was born on January 1, 1921 in the village of Zheltki, Vileisky district, Minsk region of Belarus, in a peasant family. In 1944, N. N. Malinovsky entered the Minsk Medical Institute and in 1948 graduated with honors. In 1954, he defended his thesis «Experimental observations during cardiac probing and angiocardiography». In 1957, he came to the Department of Hospital Surgery of the 1st MMI named after I. M. Sechenov at the invitation of B. V. Petrovsky, elected head of this Department. In 1964, N. N. Malinovsky defended his doctoral dissertation «Thrombosis of the left atrium and its ear in patients with mitral stenosis». In 1965, he was elected professor at the Department of Hospital Surgery of the 1st MMI, and in 1970, he became the head of the clinical department of the All-Union Research Institute of Clinical and Experimental Surgery of the Ministry of Health of the USSR (now FSBNU «Russian Scientific Center of Surgery named after acad. B. V. Petrovsky». N. N. Malinovsky’s scientific research was devoted to topical surgical problems, primarily cardiac surgery. One of the first in our country, he successfully performed embolectomy from the pulmonary artery. In addition, he was the author and co-author of more than 400 scientific papers, including 7 monographs, a practical guide to surgical diseases, one of the sections of the «Atlas of Thoracic Surgery», and a co-author of the monograph widely known among cardiovascular surgeons «Emergency Heart and Vascular Surgery» (edited by B. V. Petrovsky and M. E. DeBeiki). Academician N. N. Malinovsky – laureate of two State Prizes of the USSR (1985, 1987) and the Prize of the Russian Academy of Sciences named after A. N. Bakulev (2007), Honored Scientist of the Uzbek SSR (1979). For more than 25 years, Nikolai Nikodimovich worked as editor-in-chief of the journal «Surgery named after N. I. Pirogov», and also for many years was a member of the editorial board of the journal «Vestnik RAMS». Academician N.N. Malinovsky died on January 24, 2018 and was buried at the Troekurovsky cemetery in Moscow.